The reproductive capacity of men has declined significantly over the past 4 decades - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
From 1973 to 2011 the total sperm icount n the ejaculate decreased by 59.3% and continues to decrease by 1.6% annually.